RELEVANSI NILAI ASET TAKBERWUJUD PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dumanika Rizky Bimasakti; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This study aims to analyze the value relevance of intangible assets and value relevance from each intangible assets component (goodwill, license, and trade mark) in manufacture companies which listed on the Indonesian Stock Exchange. This study used Ohlson (1995) valuation theory with book value of equity (BVE) and earnings (EPS) as variable control. This research was conducted using secondary data which used purposive sampling as the sampling method. There are 418 companies over a three-year period of observation, a total of 73 companies chosen as a sample, with 3 samples that included outlier and should be excluded from samples of observation. So, the final samples are 70. The analytical method used is multiple linear regression analysis. The result of this research shows that: intangible assets positively and significantly affect stock price; goodwill, license, and trade mark positively effect stock price, but do not have significant affect. Those mean, when investing their money, the investor does not pay attention to each component of intangible asset in detail because they just look from the total amount of intangible asset.